Faktor-Faktor yang Berhubungan dengan Pemakaian Kontrasepsi Implant Di Puskesmas Dana Mulya Kabupaten Banyuasin Tahun 2021 - Erna Yuliarti; Syarifah Ismed; Turyani Turyani (Universitas Batanghari Jambi, 2022)
Contraception is an effort to prevent or block fertilization or the meeting between egg and sperm so that a temporary or permanent pregnancy does not occur by using a device, Implant is an effective method of hormonal contraception, not permanent and can prevent pregnancy between three to five year. The purpose of this study is to determine the relationship between Fear of Side Effects, Sources of Information, Husband's Support and Knowledge simultaneously with the use of Contraceptive Implants in Nunggal Sari Village, Dana Mulya Health Center, Banyuasin Regency in 2021. The research design that will be used in this study is descriptive analytic. with a cross sectional approach. This research was carried out in Nunggal Sari Village, Dana Mulya Public Health Center, Banyuasin Regency. The sample in this study amounted to 70 respondents. The results of Univariate analysis showed that of the 70 respondents who used implant contraceptives, 29 respondents (41.4%) and 41 respondents (58.6%) did not use implant contraceptives. From the results of the Chi-Square test, p.value is 0.026 < = 0.05 on the variable fear of side effects, the husband's support variable p.value 0.000 < = 0.05, the source of information variable p.value 0.000 < = 0, 05 dab knowledge variable p.value 0.000 < = 0.05 states that there is a statistically proven relationship between the fear of side effects, family support, sources of information and knowledge with the use of implant contraceptives. The suggestions in this study are intended for the leadership of the Puskesmas. This research can be used as input in order to increase the coverage of implant contraceptive participants, especially in the Dana Mulya Health Center Work Area, Banyuasin Regency.